Quantitative Analysis of Glyoxal, Methyl glyoxal and Dimethyl glyoxal from Foods, Beverages and Wines Using HPLC and 4-Nitro-1,2- Phenylenediamine as Derivatizing Reagent - Mahar, K.P.; Khuhawar, M.Y.; Kazi, T.G.; Abbasi, K.; Channer, A.H. (Asian Journal of Chemistry, 2010)
An analytical procedure has been developed for precolumn derivatization, separation and determination of glyoxal, methyl glyoxal and dimethyl glyoxal by HPLC using 4-nitro-1,2-phenylenediamine as a reagent. HPLC elution was from the column Zorbex C-18 and detection was by photodiode arry at 255 nm. The isocratic elution and separation was obtained with methonalwater- acetonitrile (42:56:2 v/v/v) with a flow rate 0.9 mL/min. The linearity of the calibration curves were obtained with 0.2-2.0 μg/mL with limit of detection (LOD) within 41-75 ng/mL for each of the compound. The method was used for the simultaneous determination of glyoxal, methyl glyoxal and dimethyl glyoxal from food items (juices, tea, coffee and yoghurt), beers and wines. The results were obtained with relative standard deviation (RSD) within 0.6-2.5 %.